Extreme relativistic reflection in the active galaxy ESO 033-G002 - Walton, D. J.; Balokovic, Mislav; Fabian, A. C.; Gallo, Luigi C.; Koss, M.; Nardini, E.; Reynolds, C. S.; Ricci, C.; Stern, Daniel; Alston, W. N.; Dauser, Thomas; Garcia, Javier; et al. (Monthly Notices of the Royal Astronomical Society, 2021)
We present the first high signal-to-noise broad-band X-ray spectrum of the radio-quiet type-2 Seyfert ESO 033-G002, combining data from XMM-Newton and NuSTAR. The nuclear X-ray spectrum is complex, showing evidence for both neutral and ionized absorption, as well as reflection from both the accretion disc and more distant material, but our broad-band coverage allows us to disentangle all of these different components. The total neutral column during this epoch is NH ∼(5-6) × 1022 cm-2, consistent with the optical classification of ESO 033-G002 as a type-2 Seyfert but not so large as to prevent us from robustly determining the properties of the innermost accretion flow. The ionized absorption - dominated by lines from Fe xxv and Fe xxvi - reveals a moderately rapid outflow (vout ∼5400 km s-1) which has a column comparable to the neutral absorption. We find the disc reflection from the innermost regions to be extreme, with a reflection fraction of Rfrac ∼5. This requires strong gravitational lightbending and, in turn, both an extremely compact corona (within ∼2 RG of the black hole) and a rapidly rotating black hole (a∗ > 0.96). Despite this tight size constraint, with a temperature of kTe = 40-70 keV the X-ray corona in ESO 033-G002 appears similar to other active galactic nucle in terms of its placement in the compactness-temperature plane, consistent with sitting close to the limit determined by runaway pair production. Finally, combining X-ray spectroscopy, timing, and updated optical spectroscopy, we also estimate the mass of the black hole to be log[MBH/M⊙] ∼7.0-7.5.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Black hole physics; Galaxies: active; X-rays: individual: ESO 033-G002